2001
DOI: 10.1007/s11663-001-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and three-dimensional computational fluid-dynamics modeling of the flash-converting furnace shaft: Part I. Experimental observation of copper converting reactions in terms of converting rate, converting quality, changes in particle size, morphology, and mineralogy

Abstract: An experimental investigation was conducted to elucidate the main features of the processes taking place in the shaft of a continuous flash-converting furnace for solid copper mattes. The experiments were conducted in a large laboratory furnace. The test variables included the matte grade, oxygen content in the process gas, particle size of the feed material, and oxygen-to-matte ratio. The observed variables included the fractional completion of the oxidation reactions, fraction of sulfur remaining in the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…Jokilaakso et al [11] made similar observations regarding the fraction 28 to 38 lm of chalcopyrite concentrate. During oxidation tests with high-grade copper matte particles, Perez-Tello et al [21] observed that particles of fraction <37 lm tended to increase their size upon oxidation, whereas large particles decreased their size with substantial generation of dust. In a previous study with La Caridad copper concentrate particles, Thomas et al [16] noted that particles of fraction 25 to 38 lm were less reactive than those of fraction 45 to 53 lm.…”
Section: Morphology and Reaction Path Of Particlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Jokilaakso et al [11] made similar observations regarding the fraction 28 to 38 lm of chalcopyrite concentrate. During oxidation tests with high-grade copper matte particles, Perez-Tello et al [21] observed that particles of fraction <37 lm tended to increase their size upon oxidation, whereas large particles decreased their size with substantial generation of dust. In a previous study with La Caridad copper concentrate particles, Thomas et al [16] noted that particles of fraction 25 to 38 lm were less reactive than those of fraction 45 to 53 lm.…”
Section: Morphology and Reaction Path Of Particlesmentioning
confidence: 99%
“…[2] The elucidation of the fundamental aspects governing the behavior of the flash smelting reactor may help optimize its operation in terms of energy requirements, the quality of the molten products obtained, and its potential impact on the environment, among other issues. Over the last decades, extensive experimentation has been conducted on the flash smelting [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and flash converting [18][19][20][21] processes by means of stagnant-and laminar-flow reactors. As a result, the reaction path originally proposed by Kim and Themelis [10] and further modified by Jokilaakso et al [11] and Yli-Pentila et al [20] has been widely accepted as a descriptive model which explains most of the experimental observations made under controlled laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations